Certain blood biochemicals in crossbred (Beetal x Assam local) Female Goats Fed Different levels of dietary energy - ANGAMI, M; BARUAH, K K; NATH, N C; SAIKIA, G; BARUAH, R N (The Indian Journal of Animal Reproduction, 2023)
Certain blood constituents were estimated in twelve crossbred (Beetal x Assam !ocal) female goats from weaning age (3 months) to 6 months, fed three levels of dietary energy. Energy levels had no significant effect on total serum protein, blood urea nitrogen, blood glucose, serum T 3 and T 4 values. However, values of blood glucose, T 3 and T 4 increased from low to high energy ration.